Uso de imagens digitais e smartphone para determinação de eugenol em óleo essencial do cravo-da-india (Syzygium aromaticum) - Santos, Izaura Ceolin dos (2023)
In this study, innovative and fast alternatives for determining the major constituents of clove essential oil were developed with digital images. The experiments were initially carried out using thin-layer chromatography (TLC) and, later, by colorimetry using a smartphone. The types of eluents, lighting, software, development methods, detection, and the influence of volume on the samples were previously optimized for TLC. A portable system was designed to acquire images based on the use of a smartphone, with subsequent quantification tests being made using the Photometrix app and other free software such as Image J and qTLC. The results were inaccurate due to the lack of reproducibility in analyses. Thus, colorimetry associated with the use of digital images in a smartphone was used for the determination of eugenol in clove oil. The Photometrix app was used to evaluate the colorimetric reaction between the eugenol and the Folin-Ciocalteu reagent. The results were in agreement with those obtained through traditional methodologies, such as gas chromatography and spectrophotometry, ranging from 97% to 101% for the five samples tested. The developed method allowed the analysis of several samples in a short period of time. Portability and ease of operation are also noteworthy, making it useful in the field and in places with restricted access.